REISADO CARETA: brincadeira para louvar Santo Reis - COMELIO, Paloma Sá de Castro (2009)
Analysis of mirth Reisado Careta, with music, dance, singing and poetry, performed by farmers of the Middle Itapecuru, wilderness east of Maranhão, especially in the city of Caxias. The Grimace Epiphany is a feast for kings and Holy praise is in the form of journey that symbolizes the path made by the Three Kings of Orient since the night of December 25, date of birth of Jesus Christ until the day 06 of January, when Kings came to Bethlehem The characters represented in the game vary between humans animals (donkey, ox, rooster, emu, babau), human (Nega-vein) and fantastic (jaraguaia, the faces), among others as each group brincantes present. The instruments also vary between accordion, fiddle, banjo, guitar, tambourine, triangle and drum. Creation of a cultural community is based on their traditions.